Unsafe abortion: journey from unmet needs to denial for contraception - Singh, Reeta; Shukla, Pankhuri; Aditya, Vani; Sarkar, Ruma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Easy over the counter availability of abortion pills leads to unsupervised rampant use of the pills which further results in physical and mental health complications and social and financial burdens for women, communities and health systems. Aims and objectives were to study the sociodemographic, obstetric and clinical profile of the women presenting with unsupervised intake of abortifacient, and to study the acceptance of post abortal contraception and also the method of contraception accepted. Methods: This present study was carried out in women with history of unsupervised self-intake of abortifacient and presenting with complain of bleeding per vaginum and various other complications in the emergency or outpatient department of obstetrics and gynaecology between October 2022 to September 2023 at Nehru Hospital, BRD Medical college, Gorakhpur. Complete personal, sociodemographic and obstetric history was obtained. Complete general and systemic examination was done and all routine investigations were sent. Results: A total of 197 women were enrolled in this study. In our study majority 39.48% (n=77) of women were between 25-30 years age. 56.34% (n=111) belonged to low socioeconomic strata and 69.54% (n=137) resided in urban area. 42.63% (n=84) were gravida 3 or more. 22.8% cases took abortifacient pills beyond 9 weeks of gestation. All patients procured the contraceptive from local practitioner, quacks, medical stores and chemists without any consultation from gynecologist. Most frequent complain was Chronic bleeding per vaginum with RPOC (n=112, 56.85%). Majority patients had moderate to severe anemia and 53.8% (n=106) required blood transfusion. 2.03% (n=4) presented with features of sepsis and 2.03% (n=4) presented with ruptured ectopic. Majority (n=160, 81.21%) didn’t opt for post abortion contraception. Conclusions: One major contributor to unsafe abortions is the easy availability of abortion pills. These pills should be restricted from over-the-counter sales and made available to the public only through authorized MTP centres with a proper prescription.